Psychogeography of Kuala Lumpur in Nassury Ibrahim's Selected Poems: (Psikogeografi Kuala Lumpur dalam Puisi Nasurry Ibrahim) (Malay Literature, 2017)
The strong connection between people and place provides fodder for literary producers to create their works. In his anthology of poems Ruang Kota, Nassury Ibrahim draws upon Kuala Lumpur as the place that allows him to delve into the study of self and other people. Using psychogeography as an analytical tool, this article examines how Kuala Lumpur affects the mental states and behaviors of the people living in the heart of the urban city. Nassury's poems deal with many aspects of life which include poverty, pollution and humanity. Other than his experiences, the poet uses the landscape of the city to express his own perspectives and feelings towards Kuala Lumpur. Based on the analysis, Kuala Lumpur is portrayed as a city that has developed materially but its dwellers benevolence and compassion have lessened greatly. His poems highlight urban poverty and poor urban planning in Kuala Lumpur which have led to poor quality of life in this cosmopolitan city.Keywords: psychogeography, urban poor, Kuala Lumpur